Educational Development of Indonesian Pesantren in the Perspective of Anthony Giddens’ Duality Social Change - Taufiq, Ahmad; Suryo, Djoko (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
Education in pesantren is structurally dynamic, both as a medium and as a result of the daily interactions between kiai and santri. However, this duality of structure is rarely studied in depth, giving the impression that education in pesantren is merely a finished product. This research is intended to describe the development of pesantren education in the dual social change perspective of Anthony Giddens. This research uses a qualitative approach to the literature review type, which is complemented by field research. Data was obtained using documentation and observation techniques and analyzed qualitatively. The results of the research show that education at the Bahrul Ulum Pesantren is experiencing very dynamic and complex developments. Formal education units have developed in a highly diverse manner. Likewise, pesantren units, as non-formal institutions and as places for students to live, are growing increasingly complex. This development combines preservation efforts with promoting social change. In line with Anthony Giddens' perspective, this development occurred because of the duality between the creativity of the kiai and the bunyai, as agents, and the needs and development of society, as the structure. However, this study also found something different. The existence of the pesantren as a kind of holding institution means that kiai and bunyai are not merely individual agents but are always connected to other agents interactively in determining the development of their education.